Ecos lucianescos en el Quijote: una perspectiva helenista - Montserrat Jufresa (Atalaya)
Lucian’s name never appears in the works of Cervantes. Nevertheless, scholars agree that some similar features can be recognized in the writing of both authors. The present paper aims to analyze the trace of these similarities in the structure of el Quijote: the construction of a literary theory through the novel’s development, the mix of literary genres, the permeability between reality and fiction, the confusion between truth, lies and logical reasoning, the concern about ethic values and social criticism, all written with humor and fine irony. Other points in common could be the part of friendship as a motive inside the novel, the love for freedom of main characters, the pleasure in speculations about language, or the desire of criticizing mythical tradition. We can speak probably of a more direct influence in a few episodes: the comparison of life with a dramatic performance, the presence of the world of death, the episode of the horse Clavileño, some phantasies of don Quijote and Sancho.